Optimizing Online English Language Teaching: A Post-COVID Exploration of Teaching Presence through the Lens of Thai EFL Undergraduates - Lungkapin, Kanitta (THAITESOL Journal, 2024)
During COVID-19, online education was utilized globally to bridge geographical and temporal gaps; however, this posed new challenges. In this context, instructors continued to play a crucial role in shaping students’ educational experiences and promoting student achievement. Consequently, addressing the issues that can help students adapt to significant educational changes is essential. One of the greatest challenges is identifying the new normal that will enable students and instructors to adapt to a post-COVID world. This study examined the most and least preferred indicators of teaching presence within the Community of Inquiry framework, and students’ perceptions and expectations regarding their contributions to a successful online learning experience. This study was conducted with the participation of 124 university students. Self-report questionnaires and semi-structured interviews were employed to collect data using a mix-method approach. According to the results, the most positive indicators for online students were related to clear communication—particularly regarding course topics. The least desirable indicator of teaching presence was the establishment of a learning climate. Despite difficulties such as a lack of motivation, online distractions, feelings of loneliness and isolation, online fatigue, and information overload, online learners acknowledged the importance of student-teacher relationships. This study demonstrates that online instructors can establish and sustain a strong teaching presence by communicating clearly and fostering a supportive rapport with their students. It is hoped that the findings of this study will contribute to the enhancement of the quality of online education and increase meaningful online learning experiences.